Teach yourself electricity and electronics - Gibilisco, Stan, author; Monk, Simon, author (New York : McGraw-Hill, 2016)
"This fully updated guide offers practical, easy-to-follow instruction on electricity and electronics. Written by a pair of experienced instructors, Teach Yourself Electricity and Electronics, Sixth Edition, features plain language explanations and step-by-step lessons that make it easy to understand the material quickly. Throughout, detailed illustrations, practical examples, and self-tests reinforce key concepts. Inside, you'll find all-new coverage of switching power supplies, class-D amplifiers, lithium-polymer batteries, microcontrollers--even the Arduino electronics platform."--Page [4] of cover
Part 1. Direct current. Background physics -- Electrical units -- Measuring devices -- Direct-current circuit basics -- Direct-current circuit analysis -- Resistors -- Cells and batteries -- Magnetism -- Part 2. Alternating current. Alternating-current basics -- Inductance -- Capacitance -- Phase -- Inductive reactance -- Capacitive reactance -- Impedance and admittance -- Alternating-current circuit analysis -- Alternating current power and resonance -- Transformers and impedance matching -- Part 3. Basic electronics. Introduction to semiconductors -- Diode applications -- Bipolar transistors -- Field-effect transistors -- Integrated circuits -- Electron tubes -- Power supplies -- Amplifiers and oscillators -- Wireless transmitters and receivers -- Digital basics -- Part 4. Specialized devices and systems. Microcontrollers -- Arduino -- Transducers, sensors, location, and navigation -- Acoustics and audio -- Lasers -- Advanced communications systems -- Antennas for RF communications
Includes bibliographical references and index.
Keywords: Electronics; Electricity